The Effects of Renewable Energy Sources on the Structure of the Turkish Electricity Market - Karatekin, Canan; Çelik, Hakan (International Journal of Energy Economics and Policy, 2020)
The structure of the electrical power system in Turkey has undergone rapid change and transitioned into a free market. With this development, the tendency to employ renewable energy sources (RES) has increased. In this study, both the Turkish electricity market and the renewable energy incentive structure, and the effects of RES on the electrical market have been investigated. A 10 buses power system with both traditional and renewable generator units has been considered. In this system, five different scenarios have been constructed and simulated using the PowerWorld program. Marginal prices, voltage amplitudes, voltage angles of buses and the total costs have been examined using optimal power flow (OPF). In particular, for scenarios where there was a load increase and a transmission line was disconnected, significant changes were observed in electricity prices, the voltage amplitude and the voltage angle. With the increase of RES in the electricity market, a price increase was observed in the initial stage. However, as the volume of RES gets larger, the rate of increase was observed to slow down and almost reach its previous state. Generator electricity costs have decreased and profits have increased even though retail prices have increased. The generators with increased profits have been observed to use RES. Keywords: Turkish Electricity Market, Renewable Energy Sources, Bus Marginal Price, Voltage Amplitude, Voltage Angle. JEL Classifications: Q40, Q41, L94, C61 DOI: https://doi.org/10.32479/ijeep.8896